The Effect of Musharakah Financing on Profitability at Islamic Commercial Banks in Indonesia - Arsal, Muryani; Khaliq, Abdul; Qur'ani, Nini (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2024)
This research investigates the effect of musharakah financing on the profitability of Islamic commercial banks in Indonesia over the 2017-2022 period. Musharakah financing, a partnership-based financial instrument in Islamic banking, is analyzed for its impact on the Return on Equity (ROE) ratio, a key profitability indicator. The study employs a quantitative approach, utilizing secondary data from the financial reports of nine Islamic commercial banks, resulting in 54 data points. Simple linear regression analysis, conducted using SPSS version 25, reveals that musharakah financing has a negative effect on profitability. The findings indicate that while musharakah financing is a significant Islamic banking product, it may not necessarily contribute positively to the profitability of these banks. Various factors, including the economic conditions during the study period, might have influenced these results. For instance, Indonesia faced an economic slowdown and high exchange rate fluctuations, which could have impacted the returns from musharakah financing. Additionally, the COVID-19 pandemic further strained economic activities, potentially affecting the banks' financial performance. This study's insights are crucial for Islamic commercial banks to re-evaluate their financing strategies and seek ways to enhance their ROE. Future research could expand the scope by including other Islamic financial products and extending the study period for more comprehensive results.